The role of demographic history and selection in shaping genetic diversity of the Galápagos penguin (Spheniscus mendiculus). - Gabriella Arauco-Shapiro; Katelyn I Schumacher; Dee Boersma; Juan L Bouzat (PLoS ONE)
Although many studies have documented the effects of demographic bottlenecks on the genetic diversity of natural populations, there is conflicting evidence of the roles that genetic drift and selection may play in driving changes in genetic variation at adaptive loci. We analyzed genetic variation at microsatellite and mitochondrial loci in conjunction with an adaptive MHC class II locus in the Galápagos penguin (Spheniscus mendiculus), a species that has undergone serial demographic bottlenecks associated with El Niño events through its evolutionary history. We compared levels of variation in the Galápagos penguin to those of its congener, the Magellanic penguin (Spheniscus magellanicus), which has consistently maintained a large population size and thus was used as a non-bottlenecked control. The comparison of neutral and adaptive markers in these two demographically distinct species allowed assessment of the potential role of balancing selection in maintaining levels of MHC variation during bottleneck events. Our analysis suggests that the lack of genetic diversity at both neutral and adaptive loci in the Galápagos penguin likely resulted from its restricted range, relatively low abundance, and history of demographic bottlenecks. The Galápagos penguin revealed two MHC alleles, one mitochondrial haplotype, and six alleles across five microsatellite loci, which represents only a small fraction of the diversity detected in Magellanic penguins. Despite the decreased genetic diversity in the Galápagos penguin, results revealed signals of balancing selection at the MHC, which suggest that selection can mitigate some of the effects of genetic drift during bottleneck events. Although Galápagos penguin populations have persisted for a long time, increased frequency of El Niño events due to global climate change, as well as the low diversity exhibited at immunological loci, may put this species at further risk of extinction.